Evidence is lacking for or against palmoplantar pustulosis treatments: what does this mean for the clinician. (29th November 2020) - Feldman, S.R.; Huang, W.W.
Abstract : Linked Article:  Obeid et al. Br J Dermatol 2021; 184 :1023–1032 .